2021
DOI: 10.3390/polym13213810
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polymers and Their Nanocomposites as Adsorbents in Environmental Applications

Abstract: Proper treatment and disposal of industrial pollutants of all kinds are a global issue that presents significant techno-economical challenges. The presence of pollutants such as heavy metal ions (HMIs) and organic dyes (ODs) in wastewater is considered a significant problem owing to their carcinogenic and toxic nature. Additionally, industrial gaseous pollutants (GPs) are considered to be harmful to human health and may cause various environmental issues such as global warming, acid rain, smog and air pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 151 publications
0
15
0
Order By: Relevance
“…However, producing polymers integrated with nitrogen and sulfate sites is challenging due to low yields and limited adsorption site density. Numerous studies have also utilized the acid doping and dedoping features of conductive polymers to incorporate various acid anions, achieving specific modifications and enhanced adsorption. Yet, most conductive polymers have minimal specific surface areas, constraining the amount of introduced specific sites. , Emerging structures like metal–organic frameworks (MOFs) and covalent–organic frameworks (COFs) have expansive surface areas suitable for adding numerous sites. But MOFs exhibit stability concerns, while synthesizing COFs presents formidable challenges. Our objective is to harness materials with extensive specific surface areas for site introduction, which also maintain stability and exhibit a simple synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…However, producing polymers integrated with nitrogen and sulfate sites is challenging due to low yields and limited adsorption site density. Numerous studies have also utilized the acid doping and dedoping features of conductive polymers to incorporate various acid anions, achieving specific modifications and enhanced adsorption. Yet, most conductive polymers have minimal specific surface areas, constraining the amount of introduced specific sites. , Emerging structures like metal–organic frameworks (MOFs) and covalent–organic frameworks (COFs) have expansive surface areas suitable for adding numerous sites. But MOFs exhibit stability concerns, while synthesizing COFs presents formidable challenges. Our objective is to harness materials with extensive specific surface areas for site introduction, which also maintain stability and exhibit a simple synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…4,[11][12][13] Among numerous adsorbent materials, nanocomposites based on conducting polymers, including their co-polymers, have been utilized as adsorbents and have proven to be efficient for wastewater remediation, due to their peculiar and significant characteristics, including very cheap starting material with high electrical conductivity, conjugated porous structure, easy synthesis, nontoxicity, and feasible molecular tuning. 11,[14][15][16] Despite these characteristics, the pristine polymer shows low adsorption capacity due to its crystalline behavior in the polymeric chain. Previous studies have shown that the synergistic interaction of these polymers with different metal oxides (i.e., doping), including TiO 2 , ZnO, Fe 2 O 3 , Fe 3 O 4 , and MnO 2 , leads to an enhancement of the adsorption capacity through the higher exposed specific surface area and additional adsorption sites for the adsorption of antibiotics from polluted water.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to address these issues, the conducting polymer polyaniline (PANI) has been incorporated in the blend. 8,9 Some other examples of conjugated conducting polymers are polyacetylene, polypyrrole, poly(thiophene), poly(paraphenylene vinylene) and poly(carbazole). [10][11][12] Among them, the recent emphasis on PANI is based on its incredible morphological, reactive and functional impacts upon its incorporation in the fabrication of photocatalyst composites, enhancing their spontaneous degradative activities in the photocatalysis of recalcitrant dyes, which are present in large quantities in effluents.…”
Section: Introductionmentioning
confidence: 99%
“…13 The impacts of PANI in the blend have the potential of tackling challenges of agglomeration and electron-hole recombination, which are major setbacks in photocatalysis. 9,12 Furthermore, the PANI functionally is superior to other conducting polymers due to its unique charge transport dynamics, which accounts for its high photon-sensitizing impacts, while equally enhancing the sorption activity on fabricated composites. 14,15 However, accessing the functional impacts of PANI during the fabrication of composites requires intensive microscopic and spectroscopic elucidation.…”
Section: Introductionmentioning
confidence: 99%